Examining the quality of toman fish shredded product of Tahura Lati Petangis area to increase value in commercial market - Noorma Kurnyawaty; Ibnu Eka Rahayu; Nurul Aulia (Universitas Muhammadiyah Magelang, 2021)
Tahura Lati Petangis is a forest park located in Paser Regency, East Kalimantan Province, with the management area in Batu Engau District. Tahura Lati Petangis area has a water source in the form of a lake that can be used to fulfill water resources for the surrounding area. In addition, there are also types of toman fish that have a large enough potential to be exploited. Toman fish is processed into one type of food in the form of shredded. Shredded products will be more valuable in the market if their quality and safety are guaranteed in accordance with SNI quality requirements. This service activity aims to assist community groups around the Tahura area by testing the shredded products. Through this service activity, the quality and safety of shredded toman fish products is maintained for the market, so as to increase the market value of the product. The test results showed that the shredded toman fish had met SNI standards and were free from microbial and metal contamination.